COMPARATIVE ANALYSIS OF THE DIET OF NAKED OSMAN GYMNODIPTYCHUS DYBOWSKII IN THE SHELEK AND BOROKHUDZIR RIVERS (BALKHASH BASIN, REPUBLIC OF KAZAKHSTAN) (Experimental biology, 2025)
The study and conservation of freshwater fishes is essential for the preservation and sustainability of aquatic ecosystems. The rapid decline in the diversity of native fishes is a serious threat worldwide, as it leads to the disruption of food chains and the balance of substances in natural communities. The naked osman Gymnodiptychus dybowskii is one of the most widespread native inhabitants of the foothill and mountain rivers of Central Asia. The purpose of the study was to comparatively study the nutrition of the naked osman in two rivers of the Balkash basin experiencing different anthropogenic load. Traditional ichthyological techniques of catching and processing were used for fish analysis, morphological analysis was carried out for 21 plastic features related to fish nutrition. Statistical processing was carried out using the univariate method, and the principal component method was used to compare samples. 38 objects were identified in the diet of the naked ottoman: 37 components in the Shelek River and 30 components in fish from the Borohudzir River. Feeding objects include worms, crustaceans, insect larvae, algae, higher aquatic vegetation, detritus, sand, and undefined objects. In contrast to known data, algae present a greater diversity and are an important component of the diet. Morphological differences exist between populations from the compared rivers. An important role of the naked osmanthus in the regulation of nutrient fluxes and in restraining the abundance of bloodsucking twoflies was revealed.
Keywords: Keywords: Balkhash basin, Gymnodiptichus dybowskii, naked osman, trophology, Shelek, Borohudzir, benthos, plankton